2020
DOI: 10.1159/000509451
|View full text |Cite
|
Sign up to set email alerts
|

Mortality Risk in Chronic Kidney Disease Patients Transitioning to Dialysis: Impact of Opiate and Non-Opiate Use

Abstract: Background: Population-based studies show there is a high prevalence of chronic kidney disease (CKD) patients suffering from chronic pain. While opiates are frequently prescribed in non-dialysis-dependent CKD (NDD-CKD) patients, there may be toxic accumulation of metabolites, particularly among those progressing to end-stage renal disease (ESRD). We examined the association of opiate versus other analgesic use during the pre-ESRD period with post-ESRD mortality among NDD-CKD patients transitioning to dialysis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Concern about procedural pain can cause some patients to miss follow-up appointments for regular maintenance of the dialysis access 12 . A cohort study of Veterans Affairs Healthcare System patients demonstrated an increased risk of mortality for patients with pre-ESRD using chronic opiates or pregabalin/gabapentin; secondary analysis of this study also found that patients with ESRD receiving greater than one opiate prescription per year had associated higher mortality 13 . Considering ongoing opiate misuse within the United States and data affirming higher mortality with chronic opiate use, it is imperative to begin using methods to decrease opiate-based analgesia.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Concern about procedural pain can cause some patients to miss follow-up appointments for regular maintenance of the dialysis access 12 . A cohort study of Veterans Affairs Healthcare System patients demonstrated an increased risk of mortality for patients with pre-ESRD using chronic opiates or pregabalin/gabapentin; secondary analysis of this study also found that patients with ESRD receiving greater than one opiate prescription per year had associated higher mortality 13 . Considering ongoing opiate misuse within the United States and data affirming higher mortality with chronic opiate use, it is imperative to begin using methods to decrease opiate-based analgesia.…”
Section: Discussionmentioning
confidence: 66%
“…12 A cohort study of Veterans Affairs Healthcare System patients demonstrated an increased risk of mortality for patients with pre-ESRD using chronic opiates or pregabalin/gabapentin; secondary analysis of this study also found that patients with ESRD receiving greater than one opiate prescription per year had associated higher mortality. 13 Considering ongoing opiate misuse within the United States and data affirming higher mortality with chronic opiate use, it is imperative to begin using methods to decrease opiate-based analgesia. The results from this study demonstrate that use of RA for the creation of hemodialysis access results in fewer MMEs taken by patients postoperatively.…”
Section: Discussionmentioning
confidence: 99%